Morphological Characterization of Pomegranate (Punica granatum L.) Genotypes at Dailekh - Luitel, Binod Prasad; Khanal, Asmita (Journal of Agriculture and Environment, 2023)
Pomegranate is an emerging potential fruit crop of Nepal and it can be cultivated successfully from tropical to warm temperate climatic condition of terai to mid- hills. This research was conducted to study the morphological traits and identify the superior pomegranate genotypes at Horticulture Research Station (HRS), Dailekh in 2019. Three pomegranate genotypes (HRDPOM001, HRDPOM004 and HRDPOM004M) were studied for their growth, flowers and pomological characters. Variation in plants, flower and pomological characters was observed in pomegranate genotypes. The highest marketable fruit weight (1.4 kg/plant) produced in HRDPOM001, followed by HRDPOM004 (1.2 kg/plant). The highest aril weight (60.5%) was measured in HRDPOM004. Highest TSS (12.8°Brix) and good taste preferences were recorded in the fruits of HRDPOM004. Pomological attributes for HRDPOM004 was found better than other studied genotypes. Individual fruit weight, fruit length, and fruit diameter showed the significant positive association with total fruit weight, and selection of these traits could improve the fruit yield. Based on the major pomological attributes, HRDPOM004 was found promising and selected to cultivate at the similar agro-climatic regions of Nepal.